2022
DOI: 10.1108/jeas-09-2021-0175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of microfinance institutions in enhancing the livelihood of urban poor

Abstract: PurposeThe goal of this research is to look at how urban microfinance affects livelihood transformation in terms of poverty reduction, living standards, social well-being, empowerment and entrepreneurship.Design/methodology/approachThis paper analyses the role of urban microfinance towards livelihood with special reference to Western Uttar Pradesh. Primary data were collected from 321 respondents who are users of a microfinance programme using a standardised questionnaire. The data were collected using a strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Findings from another study of nationally representative survey data, the China Family Panel Studies, analyzed using an endogenous switching probit model that accounts for selection bias for both observed and unobserved factors, suggested that access to credit stimulates farmers' decisions to participate in farmland rental markets by increasing the likelihood of renting in farmland by 10% and of renting out by about 20% (Li et al, 2020). Literature on the spread of microfinance in urban areas shows a considerable impact on poverty reduction, standard of living, social well‐being, empowerment, and entrepreneurship among the urban poor (see, for instance, Hasan et al, 2022). In another recent study, Bel Hadj Miled (2023) found access to credit to have a positive and significant impact on Tunisian women's work, attitudes toward income increase, execution of microprojects, and schooling attendance.…”
Section: Related Literature On Microcredit and Women's Empowermentmentioning
confidence: 99%
“…Findings from another study of nationally representative survey data, the China Family Panel Studies, analyzed using an endogenous switching probit model that accounts for selection bias for both observed and unobserved factors, suggested that access to credit stimulates farmers' decisions to participate in farmland rental markets by increasing the likelihood of renting in farmland by 10% and of renting out by about 20% (Li et al, 2020). Literature on the spread of microfinance in urban areas shows a considerable impact on poverty reduction, standard of living, social well‐being, empowerment, and entrepreneurship among the urban poor (see, for instance, Hasan et al, 2022). In another recent study, Bel Hadj Miled (2023) found access to credit to have a positive and significant impact on Tunisian women's work, attitudes toward income increase, execution of microprojects, and schooling attendance.…”
Section: Related Literature On Microcredit and Women's Empowermentmentioning
confidence: 99%
“…This shift is driven by the need to adhere to regulatory mandates and to exploit emerging market segments. Microfinance institutions are dedicated to supplying modest loans and related financial services to those with low incomes and micro-entrepreneurs (Hasan et al, 2022). Non-profit organizations frequently operate as intermediaries, harnessing their community connections to advance financial inclusivity (Bals et al, 2023).…”
Section: Market Playersmentioning
confidence: 99%
“…In a context where the world economy is headed by women, The United Nations has identified women's empowerment as one of its top priorities for the coming years. (Hasan, 2022), But on the contrary, the COVID-19 pandemic has had a detrimental impact on entrepreneurship in the last decade. According to O'Donnell et al (2021), womenowned businesses have been more likely to get close since the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%